ANALISIS PERBANDINGAN KONDISI FINANCIAL DISTRES0S PADA PERUSAHAAN ASURANSI JIWA SYARIAH DI INDONESIA DAN MALAYSIA BERDASARKAN MODEL DISKRIMANASI ALTMAN - Tri Mei Wulandari; Dina Fitrisia Septiarini (Universitas Airlangga, 2018)
The purpose of this research is to know the difference of financial distress condition of sharia life insurance company in Indonesia and in Malaysia in period 2013-3105 with Atman Zscore model. Using a quantitative approach with Mann Whitney's test. Sampling method using purposive sampling. This study uses secondary data taken from the official website of each company. The data used are the company's financial statements covering balance sheet, and income statement. The results of the Altman Z-score discriminant model were then tested using spss version 22. Mann Whitney test results showed that there was a significant difference between the financial distress condition of sharia life insurance companies in Indonesia and Malaysia. The results of this study proves that the condition of sharia life insurance companies in Indonesia is better than in Malaysia. REFERENCESAmrin, Abdullah. 2006. Asuransi Syariah Keberadaan dan Kelebihannya di Tengah Asuransi Konvensional. Jakarta: PT.Elex Media KomputindoMamduh, Hanafi. 2009. Manajemen Risiko. Yogyakarta: Unit Penerbit dan Percetakan Sekolah Tinggi Ilmu Manajemen YKPN. Salim, Abbas. 2005. Asuransi & Manajemen Risiko. Jakarta: PT. Raja Grafindo. Soemitra, Andri. 2009. Asuransi Syariah. Medan: Wal Ashri PublishingShihab, Quraish. 2002. Tafsir Al Misbah. Jakarta.Umar, Husein.1998. Manajemen Risiko Bisnis. Jakarta: PT. Gramedia Pustaka Utama.Vira, Eneng Asia. 2015. Pengaruh Rasio Keuangan terhadap Prediksi Kebangkrutan (Altman Z-score)Industri Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Tahun 2009-2011.Jurnla Visionida, Vol. 1 No. 1.